2015
DOI: 10.1155/2015/683895
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraocular Pressure before and after Laser In Situ Keratomileusis Refractive Surgery Measured with Perkins Tonometry, Noncontact Tonometry, and Transpalpebral Tonometry

Abstract: Purpose. To compare the intraocular pressure (IOP) before and after Laser In Situ Keratomileusis (LASIK), measured by Diaton, Perkins, and noncontact air pulse tonometers. Methods. Fifty-seven patients with a mean age of 34.88 were scheduled for myopia LASIK treatment. Spherical equivalent refraction (SER), corneal curvature (K), and central corneal thickness (CCT) and superior corneal thickness (SCT) were obtained before and after LASIK surgery. IOP values before and after surgery were measured using Diaton, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Moreover, CCT remained stable at 3 months and corneal curvature kept changing. Although some studies showed that the corneal curvature and CCT were related to IOP reduction, 15,28 Liu and Roberts 29 reported that differences in corneal biomechanics between individuals may contribute more than corneal thickness or curvature to IOP measurement errors, which was consistent with this study. After surgery, patients needed routine application of 0.1% FML to prevent inflammation and refractive regression for 2 months.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, CCT remained stable at 3 months and corneal curvature kept changing. Although some studies showed that the corneal curvature and CCT were related to IOP reduction, 15,28 Liu and Roberts 29 reported that differences in corneal biomechanics between individuals may contribute more than corneal thickness or curvature to IOP measurement errors, which was consistent with this study. After surgery, patients needed routine application of 0.1% FML to prevent inflammation and refractive regression for 2 months.…”
Section: Discussionsupporting
confidence: 89%
“…The unsatisfactory results of these approaches may be attributed to changes in biomechanics, which are considered basic parameters for these devices. [13][14][15][16][17][18][19][20] Because of the inaccuracy of GAT measurements following LASIK, there is an argument for the development of a correction formula to address this issue. The development of a correction formula has been suggested by several authors previously, but none of the proposals has so far gained wide acceptance or been considered suitable for application.…”
Section: Discussionmentioning
confidence: 99%
“…IOP values before scleral CL wear were assessed by both GAT (Haag-Streit AT900, USA) and DT (BICOM Inc, Long Beach, NY, USA), to have comparable measurements before and after the contact lenses wear. 13 …”
Section: Methodsmentioning
confidence: 99%